Herpes zoster prophylaxis: Essential for treating newly diagnosed multiple myeloma patients - Wen‐Ying Lin; Chun‐Kuang Tsai; Chiu‐Mei Yeh; Tin Chian; Yao‐Chung Liu; Hao‐Yuan Wang; Po‐Shen Ko; Ting‐An Lin; Liang‐Tsai Hsiao; Po‐Min Chen; Jyh‐Pyng Gau; Chia‐Jen Liu (Cancer Medicine)
Abstract Background Multiple myeloma (MM) is known for its immune disturbance and patients suffering from MM are thus vulnerable to opportunistic infections, including herpes zoster (HZ). As HZ infection remarkably affects patients' quality of life and poses huge economic burdens on the health system, we aim to identify the risk factors of HZ infection and evaluate the effects of different dosages, types, and durations of anti‐HZ prophylaxis drugs to prevent HZ infection. Methods 551 MM patients at Taipei Veterans General Hospital in Taiwan between January 1, 2009 and August 31, 2021 were restrospectively analyzed. The patients' baseline characteristics were recorded. The primary endpoint of the study was the incidence of HZ infection among the studied patient population. Due to the lack of cost coverage from Taiwanese public health insurance on HZ prophylaxis drugs, the use of anti‐HZ drugs mainly depends on physicians' preferences and patients' choices. Results In our study, prophylaxis was given to 283 of the patients. In the multivariate analysis, we included non‐prophylaxis, age ≥ 60, corrected serum calcium ≥12 mg/dl, serum creatinine ≥2 mg/dl, serum β2‐microglobulin ≥5500 mg/L, autologous stem cell transplant (SCT), and allogeneic SCT for analysis. Our results demonstrated that the non‐prophylaxis group (HR: 2.37, 95% CI 1.57–3.57) and patients receiving autologous SCT (HR: 2.22, 95% CI 1.28–3.86) and allogeneic SCT (HR: 5.12, 95% CI 1.13–23.22) had higher risk of HZ infection. The difference in dosage and types of anti‐HZ drugs showed similar protective effects. In patients who stopped anti‐HZ prophylaxis before active cancer‐related treatment, a higher risk of getting HZ infection compared to the corresponding group was also observed (adjusted HR 3.09, 95% CI 1.35–7.07, p = 0.008). Conclusions We concluded that MM patients should receive HZ prophylaxis drugs while receiving active cancer‐related treatment. Patients receiving SCT are also at high risk of getting HZ infection, even under prophylaxis.